Eficacia de la terapia de reemplazo de vitamina D en pacientes con fibromialgia - Cholán Caruajulca, Cynthia Aurora (2022)
Introduction: Fibromyalgia (FM) is a disorder characterized by chronic and widespread musculoskeletal pain, often associated with debilitating fatigue, unrefreshing sleep, lack of recognition, depression and anxiety due to an innocuous stimulus that is usually not painful) and hyperalgesia (ie, exaggerated pain caused by a noxious stimulus)(1). Globally, the mean prevalence of FM is 4.2% in women and 1.4% in men, with a female/male ratio of 3:1. Vitamin D is an important regulator of the immune system, acting as an active cofactor in the incidence of autoimmune disorders such as multiple sclerosis, rheumatoid arthritis, insulin-dependent diabetes mellitus, and irritable bowel syndrome. Vitamin D deficiency is defined as a serum level of 25-hydroxy vitamin D that is less than 25 ng/ml (50 nmol/ml)(3). There is no consensus on the association between vitamin D and FM. Several studies have mentioned the correlation between low vitamin D concentration and nonspecific musculoskeletal pain, while other studies reported the likely association between vitamin D deficiency and clinical manifestations of FM. However, other studies did not find any significant association between FM and vitamin D(4)(5). In accordance with the discrepancies mentioned above between the results of the primary studies, our objective will be to evaluate the efficacy of vitamin D supplementation on patients with fibromyalgia who have a deficiency of this vitamin.